Seizure Semiology Over Time in Adult Diffuse Glioma. (1st October 2022) - Carstairs, Claire; Pandey, Anmol; Moulder, Zachary; Kosela, Monika; Rees, Jeremy
Abstract: AIMS: Patients with gliomas often present with generalised seizures, but subsequently develop focal seizures on treatment. The occurrence of a single generalised seizure at onset precludes the return of a driving licence, even if a patient continues to have only focal aware seizures. We investigated seizure semiology over time, to determine how many patients with ongoing seizures may be safe to drive. METHOD: We analysed clinical data of patients with histologically-confirmed IDH-mutant diffuse gliomas, diagnosed between 2004-2015. Seizures were classified as: 1 – focal / 2 - generalised; A – aware / B – unaware; M – motor / N – non-motor. Seizure type at diagnosis and last follow-up was recorded. RESULTS: 189 patients were identified, of whom 140 presented with seizures (74%). 115 of these patients had a full data set. 59 (51%) presented with generalised seizures. 10% had only a single seizure at presentation, 55 % had further seizures then became seizure-free and 35% continued to have seizures at last follow-up. Of the 40 patients who continued to have seizures, 7 (17.5%) had 1AN, 16 (40%) had 1AM, 1 (2.5%) had 1BN and 5 (12.5%) had 1BM. 11 (27.5%) had generalised seizures. Of the 7 patients with 1AN seizures at last follow-up, 4 initially presented with a generalised seizure, 1 with 1AN, 1 with 1AM and 1 with 1BM. CONCLUSION: Almost two thirds of patients became seizure-free and, of those that continued to have seizures, 57.5% developed only focal aware seizures. Current driving regulations may be unduly restrictive for patients with gliomas.